Data structures and abstractions with Java - Carrano, Frank M.; Henry, Timothy M. (Pearson Education Limited, 2016)
This is the most student-friendly data structures text available that introduces ADTs in individual, brief chapters - each with pedagogical tools to help students master each concept. Using the latest features of Java, this unique object-oriented presentation makes a clear distinction between specification and implementation to simplify learning, while providing maximum classroom flexibility.